Compassion fatigue, psychological resilience, moral sensitivity, and humanistic caring ability in clinical nurses: a structural equation model - Shuqi Zhai; Qinqin Liu; Congcong Dai; Yifan Lu; Huanhuan Zhang; Jie Liu; Chaoran Chen (BMC Nursing)
Abstract Background The level of nursing humanistic caring ability, as a core topic in the development of nursing discipline, directly affects the quality of nursing services and patient health outcomes. Although existing studies have focused on the negative impact of compassion fatigue on nursing staff’s professional status, the intrinsic mechanism of its role with humanistic caring ability has not been systematically elucidated, and in particular, the mediating role of compassion fatigue and clinical nurses’ humanistic caring ability still lacks empirical evidence. In view of this, the present study aimed to investigate the effects of compassion fatigue on clinical nurses’ humanistic caring ability and its mediating role, with a view to providing a theoretical basis for optimizing nurses’ mental health management and humanistic literacy training. Objective This study aimed to construct and empirically test a structural equation model to clarify the pathways through which compassion fatigue affects clinical nurses’ humanistic caring ability. Specifically, it investigated whether psychological resilience and moral sensitivity serve as mediating variables in this relationship, thereby providing theoretical and empirical support for interventions to enhance nurses’ humanistic caring ability in clinical settings. Methods This study employed the the Compassion Fatigue Scale, the Nurses’ Humanistic Caring Ability Scale, the Psychological Resilience Scale, and the Moral Sensitivity Questionnaire to survey 724 clinical nurses from three general hospitals in Henan Province, China, between June and September 2024.Data analysis was conducted using SPSS 25.0, while AMOS 26.0 was utilized for model mapping and mediation path analysis. Results Compassion fatigue was a significant negative predictor of their humanistic caring ability (r= -0.537, P < 0.01), and psychological resilience and moral sensitivity acted as chain mediators between compassion fatigue and humanistic caring ability (β= -0.015, P < 0.01). Conclusions Clinical nurses’ compassion fatigue was significantly associated with their humanistic caring ability, with psychological resilience and moral sensitivity acting as chain mediators between the two. Therefore, hospital administrators should pay attention to the situation of nurses’ compassion fatigue and humanistic caring ability, and develop a series of targeted measures to enhance their humanistic caring ability with psychological resilience and moral sensitivity as the entry point. Clinical trial number Not applicable.